Investment Regulation and Guarantee in Coastal Area and Small Islands in North Sulawesi Province - Amalia; Kalalo, Merry E; Anis, Friend H. (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2021)
Abstract: This study aims to analyze the regulation and guarantee in the implementation of investment in coastal areas and small islands by local governments as well as how to supervise and control investment activities in coastal areas and small islands as well as the authority of the Regional Government to stop and revoke the investment permit. The normative legal research method is used to examine in depth the regulation and guarantee of the Regional Government in the implementation of investment in the coastal area of ​​North Sulawesi. In order to obtain data in this study, data collection techniques are needed to obtain primary data and secondary data, both of which will be analyzed. The data collection technique used in this research is literature study. The result of the research shows that the local government is still not optimal in the court of investment activities in the Coastal area of ​​North Sulawesi. As a result of this, investment cases arise. The famous cases of investment in the Coastal Area are the Buyat Bay case or the coastal area pollution case by PT Newmont Minahasa Raya, the iron ore exploration case on the North Minahasa island of Bangka by PT MMP whose case went to the Supreme Court with the Supreme Court decision Number 255 of 2016 which won the community and revoke PT MMP's activities on the island of Bangka. But until now the company has carried out its activities and the community continues to struggle. The third case is PT MSM which, although it has been rejected and dismissed by the North Sulawesi DPRD in 2016 but is still operating until now. In investment activities in coastal areas, from these cases, the government tends to neglect and does not take action to stop the company's activities. Keywords: Arrangement; Guarantee; Investment